KETIDAKLENGKAPAN DOSCHARGE SUMMARY DAN LAMA PENGEMBALIAN BERKAS REKAM MEDIS DALAM PENINGKATAN MUTU PELAYANAN REKAM MEDIS DI RS X BANDUNG - Amalia Dwi Astari; Dina Sonia (Universitas Pahlawan Tuanku Tambusai, 2021)
Hospitals are a complex institution of health care, because hospital service involves various functions of service, education, and research, and covers a wide range of degrees and kinds of discipline. To enable hospitals to perform professional functions both in the field of medical engineering and in health administration. Hospital maintenance and improvement requires that it have a measure of quality at all levels. The purpose of this study is to know the incompletion review of discharge summary and the long retrieval of medical record files. The method the writer is a quantitative descriptive,50 files of medical records were taken, Analysts used were observation and interview, The subjects in this study are doctors and medical recorders. The results of this study amounted to 79% complete medical records and 21% incomplete files. 75% of files returned on time, and 25% of files returned intime. It seems that hospital x has filled the SOP and the technical instructions are in place. The incompleteness of medical record files greatly affects the quality of hospital health care. It is therefore expected that all officers will be able to perform their duties according to the SOP in the hospital and increase the number for the medical record file. Hospitals can maintain the quality of service for inpatients and outpatients. Word key : discharge summary, hospital, medical record.